“Crash”-ing into Pop Culture in Dealing with Diversity: Adult Education and Critical Media Literacy about Movies and Television - Elizabeth J. Tisdell; Patricia M. Thompson (Adult Education Research Conference, 2006)
This paper reports on the qualitative component of a study of what adult educators and adult learners “learn” about themselves and others based on portrayals of characters in film and television more generally, with particular attention to the recent Paul Haggis film “Crash.”